2008
DOI: 10.3358/shokueishi.49.261
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Viable Salmonella Cell Numbers in Meat and Meat Product Using Real-Time PCR

Abstract: Recently we developed a novel method for estimating viable Salmonella cell numbers by means of a 5῎-nuclease real-time PCR [Fujikawa et al., J. Food Hyg. Japan, 47, 151ῌ156 (2006)]. The method was based on the increase kinetics of the target DNA region (inv A) of the microorganism growing in a culture medium during incubation. The index for the PCR was the threshold cycle. In this study, we validated the method for application in food. Namely, Salmonella cells spiked into ground chicken, pork, and beef and raw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The numbers of Salmonella in our study varied from less than 1 to 4 log 10 CFU/g for 134 samples. Nevertheless, no spoilage was observed in the poultry meat before processing and it was thought that competition among the micro-organisms in the poultry meat might suppress the growth of Salmonella cells [8]. A previous study showed that inoculated 10 5 CFU/g of Salmonella cells in minced meat, they grew to a high population level (10 9 CFU/g) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of Salmonella in our study varied from less than 1 to 4 log 10 CFU/g for 134 samples. Nevertheless, no spoilage was observed in the poultry meat before processing and it was thought that competition among the micro-organisms in the poultry meat might suppress the growth of Salmonella cells [8]. A previous study showed that inoculated 10 5 CFU/g of Salmonella cells in minced meat, they grew to a high population level (10 9 CFU/g) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently studies have been carried out to determine the suitability of using RNA to quantify pathogens by real-time reversetranscriptase PCR (real-time RT-PCR) (McCabe et al, 2011a(McCabe et al, , 2011bMiller, Davidson, & D'Souza, 2011, Miller, Draughon, & D'Souza, 2010. However most of these methods required one-or two-step enrichments prior to real-time RT-PCR in order to detect a small number of target cells (Fujikawa & Shimojima, 2008). Until now, rapid detection of viable L. monocytogenes without enrichments in chilled pork by real-time RT-PCR has not been reported.…”
Section: Introductionmentioning
confidence: 99%